Mental content - Schulte, Peter (Cambridge elements, 2023)
This Element introduces contemporary theories of mental content. It considers recent developments in the debate, specifically the 'explanatory turn' and its implications for questions about representations in basic cognitive systems and the representational character of current empirical theories of cognition